Supply‐controlled calcium carbonate dissolution decouples the seasonal dissolved oxygen and pH minima in Chesapeake Bay - Jianzhong Su; Wei‐Jun Cai; Jeremy M. Testa; Jean R. Brodeur; Baoshan Chen; K. Michael Scaboo; Ming Li; Chunqi Shen; Margaret Dolan; Yuan‐Yuan Xu; Yafeng Zhang; Najid Hussain (Limnology and Oceanography, 2021)
Acidification can present a stress on organisms and habitats in estuaries in addition to hypoxia. Although oxygen and pH decreases are generally coupled due to aerobic respiration, pH dynamics may be more complex given the multiple modes of buffering in the carbonate system. We studied the seasonal cycle of dissolved oxygen (DO), pH, dissolved inorganic carbon, total alkalinity, and calcium ion (Ca 2+ ) along the main channel of Chesapeake Bay from May to October in 2016. Contrary to the expected co‐occurrence of seasonal DO and pH declines in subsurface water, we found that the pH decline ended in June while the DO decline continued until August in mid‐Chesapeake Bay. We discovered that aerobic respiration was strong from May to August, but carbonate dissolution was minor in May and June and became substantial in August, which buffered further pH declines and caused the seasonal DO and pH minima mismatch. The rate of calcium carbonate (CaCO 3 ) dissolution was not primarily controlled by the saturation state in bottom water, but was instead likely controlled by the supply of CaCO 3 particles. The seasonal variability of Ca 2+ addition in the mid‐bay was connected to Ca 2+ removal in the upper bay, and the timing of high carbonate dissolution coincided with peak seasonal biomass of upper Bay submerged aquatic vegetation. This study suggests a mechanism for a novel decoupling of DO and pH in estuarine waters associated with CaCO 3 , but future studies are needed to fully investigate the seasonality of physical transport and cycling of CaCO 3 .